Consumption of Galacto-Oligosaccharides Increases Iron Absorption from Ferrous Fumarate: A Stable Iron Isotope Study in Iron-Depleted Young Women. Issue 5 (20th April 2019) - Jeroense, Frederike M D; Michel, Ladina; Zeder, Christophe; Herter-Aeberli, Isabelle; Zimmermann, Michael B
ABSTRACT: Background: Animal studies suggest prebiotics can increase iron absorption, but results from human studies are equivocal. Objectives: In iron-depleted women, before (baseline) and after daily consumption of galacto-oligosaccharides (GOS) for 4 wk, we sought to assess fractional iron absorption (FIA) from an iron supplement given with and without single doses of GOS in test meals or water. Methods: In all women ( n = 34; median serum ferritin concentration = 16.4 µg/L), FIA from doses of 14 mg iron labeled with stable isotopes was measured in the following conditions at baseline: 1 ) FIA from ferrous fumarate (FeFum) in water given with and without 15 g GOS; 2 ) FIA from FeFum in a test meal given with and without 15 g GOS; 3 ) FIA from ferrous sulfate (FeSO4 ) in a test meal given without 15 g GOS. All subjects then consumed ∼15 g GOS daily for 4 wk. Then the following conditions were tested: 4 ) FIA from FeFum in a test meal with and without 15 g GOS; and 5 ) FIA from FeSO4 in a test meal with 15 g GOS. FIA was measured as erythrocyte incorporation of stable isotopes. Results: At baseline, GOS significantly increased FIA from FeFum when given with water (+61%; P < 0.001) and the meal (+28%; P = 0.002). After 4 wk of GOS consumption, GOS again significantly increased FIA from FeFum in the meal (+29%; P = 0.044). However, compared with baseline, consumption of GOS for 4 wk did not significantly enhance absorption from FeFum in the meal given without GOS. FIA from FeSO4 given with GOS in a meal after 4 wk of GOS consumption was not significantly greater than FIA from FeSO4 in a meal without GOS at baseline. Conclusions: In iron-depleted women, GOS given with FeFum increases FIA, but 4 wk of GOS consumption did not enhance this effect. The study was registered at clinicaltrials.gov as NCT03325270.